2016
DOI: 10.1371/journal.pone.0161059
|View full text |Cite
|
Sign up to set email alerts
|

A Look into the Cell: Honey Storage in Honey Bees, Apis mellifera

Abstract: Honey bees, Apis species, obtain carbohydrates from nectar and honeydew. These resources are ripened into honey in wax cells that are capped for long-term storage. These stores are used to overcome dearth periods when foraging is not possible. Despite the economic and ecological importance of honey, little is known about the processes of its production by workers. Here, we monitored the usage of storage cells and the ripening process of honey in free-flying A. mellifera colonies. We provided the colonies with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 27 publications
0
26
0
Order By: Relevance
“…Since the last two decades, honey has been explored for its gastroprotective, hepatoprotective, reproductive, hypoglycemic, antioxidant, antihypertensive, antibacterial, antifungal, anti-inflammatory, immunomodulatory, wound healing, cardioprotective, and antitumor effects [33][34][35][36][37][38][39][40]. In general, pure honey contains over 200 compounds, consisting mainly of carbohydrates (monosaccharides: glucose and fructose; disaccharides: sucrose and maltose), protein (amino acids and enzymes), minerals, vitamins (vitamin B6, riboflavin, niacin, and thiamine), phenolic compounds (flavonoids and phenolic acids), and volatile substance (responsible for the characteristic aroma of honey) [41][42][43][44][45][46]. In kainic acid-induced excitotoxicity animal model, pretreatment with honey significantly attenuated oxidative stress, neuroinflammation, and apoptosis in the cerebral cortex, cerebellum, and brainstem as well as progression of neuronal damage in the piriform cortex of kainic acid-induced rats [47][48][49].…”
Section: Neuroprotective Activities Of Natural Products and Their Biomentioning
confidence: 99%
“…Since the last two decades, honey has been explored for its gastroprotective, hepatoprotective, reproductive, hypoglycemic, antioxidant, antihypertensive, antibacterial, antifungal, anti-inflammatory, immunomodulatory, wound healing, cardioprotective, and antitumor effects [33][34][35][36][37][38][39][40]. In general, pure honey contains over 200 compounds, consisting mainly of carbohydrates (monosaccharides: glucose and fructose; disaccharides: sucrose and maltose), protein (amino acids and enzymes), minerals, vitamins (vitamin B6, riboflavin, niacin, and thiamine), phenolic compounds (flavonoids and phenolic acids), and volatile substance (responsible for the characteristic aroma of honey) [41][42][43][44][45][46]. In kainic acid-induced excitotoxicity animal model, pretreatment with honey significantly attenuated oxidative stress, neuroinflammation, and apoptosis in the cerebral cortex, cerebellum, and brainstem as well as progression of neuronal damage in the piriform cortex of kainic acid-induced rats [47][48][49].…”
Section: Neuroprotective Activities Of Natural Products and Their Biomentioning
confidence: 99%
“…Lithium is delivered to the honeybee colony dissolved in feed (e.g., sucrose syrup), which is transformed to the primary form of carbohydrate storage, the honey, thus linking the honeybee and human food chains. It has often been demonstrated that honeybee feed ends up in extracted honey due to the storage behavior of honeybees (Eyer et al, 2016), making food chain coupling likely. The present paper addresses some of the concerns above, namely lithium presence in honey, in bee bread, and in honeybee larvae due to feeding with sucrose syrup containing dissolved lithium chloride.…”
Section: Introductionmentioning
confidence: 99%
“…The sucrose syrup is transformed by workers into honey and stored in the brood chamber. Leftover food stores are a possible source of contamination: it is well known phenomenon that honeybees transfer honey stores between combs and hive compartments, especially in season during the honey flow when bees transfer stores during the process of nectar conversion to honey and drying(Eyer et al, 2016, Kandolf- Borovšak, 2019…”
mentioning
confidence: 99%
“…Another field with considerable usage of X-ray CT is the study of social insects and their nest or gallery systems. Here, images are primarily acquired in vivo allowing to scan the same nest or colony several times during its developmental cycle (Eyer, Neumann, & Dietemann, 2016 Establishment of trophic relationships in extant (Herrel et al, 2010;Kato et al, 2014;Pampush et al, 2016;Renaud et al, 2015;Self, 2015;Soons et al, 2015) and extinct species (Collareta et al, 2015;Gill et al, 2014) has also been possible by analysis of gut content, beak shape, or dental wear patterns.…”
Section: Interestingly Ecology Was Included As "Environmental Sciencesmentioning
confidence: 99%